3-Dimensional Model to Study Apoptosis Induction of Activated Natural Killer Cells Conditioned Medium Using Patient-Derived Colorectal Cancer Organoids - Parseh, Benyamin; Khosravi, Ayyoob; Fazel, Abdolreza; Ai, Jafar; Ebrahimi-Barough, Somayeh; Verdi, Javad; Shahbazi, Majid (Frontiers in Cell and Developmental Biology, 2022)
Natural killer (NK) cells are innate lymphocytes that can kill tumor cells via different pathways, including the secretion of cytotoxic granules in immunological synapses and the binding of apoptosis-inducing ligands with cognate death receptors on tumor cells. These ligands also present as a soluble form in NK cells conditioned medium (NK-CM). However, novel preclinical in vitro models are required for solid tumors such as colorectal cancer (CRC) to investigate apoptosis induction of activated NK-CM in a tissue-like structure. In the present study, we established a patient-derived CRC organoid culture system as a new tool for CRC research in the last decade. Tumor organoids were stained with hematoxylin and eosin (H&E) and compared with the original tumor taken from the patient. Goblet cell differentiation and mucus secretion were evaluated using periodic acid–schiff and alcian blue histochemical staining. Moreover, tumor organoids were stained for CDX2 and Ki67 markers with immunohistochemistry (IHC) to investigate gastrointestinal origin and proliferation. Histopathological evaluations indicated tumor organoids represent patient tumor characteristics. Primary NK cells were isolated, and further ex vivo expansion, IL-2-activated NK-CM was collected. To characterize activated NK-CM, secretion of IFN-λ and TNF-α were measured. In comparison to the control group, cytokines levels were significantly elevated. Also, soluble forms of apoptosis-inducing ligands, including TNF-related apoptosis-inducing ligand (TRAIL) and FasL, were detected by western blot assay. Then the cell-free conditioned medium was treated to the treatment group. Apoptosis induction was considered by FITC/PI staining and quantified by flow cytometry. The result demonstrated no significant changes in apoptosis induction of colon cancer organoids. In conclusion, despite the activated NK-CM containing apoptosis-inducing ligands, these ligands' soluble forms cannot induce apoptosis in colon cancer organoids. Nevertheless, we report a reliable in vitro assessment platform in a personalized setting.